Islamic Entrepreneurship: A Systematic Review of Future Challenges and Prospects of Pakistani SMEs - Khalique, Muhammad; Ramayah, T; Hina, Khushbakht; Shaari, Jamal Abdul Nassir (International Journal of Economics, Management and Accounting, 2020)
The main objective of this study is to provide a framework of IslÄmic entrepreneurship for Pakistani SMEs to address their issues within a knowledge-based economy perspective. The paper reviews contemporary literature and the Holy QurÊ¾Än verses, the Prophet Muhammadâ€™s (á¹£al-AllÄhu Ê¿alayhi wa sallam) HadÄ«th (sayings) and Sunnah (practice) on IslÄmic entrepreneurship, for establishing a business model for entrepreneurs. On the basis of extensive literature reviews and evidence, the study proposed a business model of IslÄmic entrepreneurship which is mainly based on two dimensions namely business perspective and spiritual perspective. The paper is conceptual in nature. There is a need for developing a measurement scale to measure the business model of IslÄmic entrepreneurship. IslÄmic entrepreneurship is considered as the most crucial topic in business solutions because of the very complex and dynamic business environment. In the present business environment, the role of religion and culture is very important for the success of SMEs. The proposed business model of IslÄmic entrepreneurship will help Pakistani SMEs to understand the halal and haram concept in more depth. Moreover, they would be able to capitalize the IslÄmic rules and principles in their business. The novelty of this study lies in expanding the existing research on the link between IslÄmic entrepreneurship and the future challenges and prospects of Pakistani SMEs. The proposed business model of IslÄmic entrepreneurship is unique and it will guide development of the scale to measure IslÄmic entrepreneurship in organizations. This is arguably a first study contributing to IslÄmic entrepreneurship literature in the Pakistani context.Â Â